Point and shoot: police media labor and technologies of surveillance in End of Watch - McVey, James Alexander (Crime, media, culture, 2022)
This article analyzes the 2012 found-footage buddy-cop film End of Watch. The author analyzes the film’s production, plot, para-textual materials, audience reviews, and audience-generated media to examine the film’s rhetorical strategies and cultural impact. The author shows how police media work inspired the film’s creation, influenced the film’s production, and shaped the film’s messages. End of Watch is a crucial test case for understanding how police collaborate with the entertainment industry to respond to public crises of police visuality. Police media labor shaped the creation, production, and performances of the film, helping create a media product branded simultaneously as a realistic look at police life and a positive correction to negative media representations of police officers. End of Watch breathes cinematic life into commonplace hegemonic tropes of police backlash rhetoric. This article argues that End of Watch uses surveillant narration to humanize police and dehumanize the subjects of police violence. It also demonstrates how End of Watch served as a source of rhetorical invention for pro-police publics who drew on images and tropes from the film to defend police in the face of the crises of police visibility that emerged in the years following the film’s release.